2016
DOI: 10.1103/physrevb.94.184406
|View full text |Cite
|
Sign up to set email alerts
|

Role of electron and phonon temperatures in the helicity-independent all-optical switching of GdFeCo

Abstract: Ultrafast optical heating of the electrons in ferrimagnetic metals can result in all-optical switching (AOS) of the magnetization. Here we report quantitative measurements of the temperature rise of GdFeCo thin films during helicity-independent AOS. Critical switching fluences are obtained as a function of the initial temperature of the sample and for laser pulse durations from 55 fs to 15 ps. We conclude that non-equilibrium phenomena are necessary for helicity-independent AOS, although the peak electron temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
94
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 37 publications
12
94
0
1
Order By: Relevance
“…However, while we have demonstrated that T M is not an essential criteria for switching, the results so far do not confirm that it is an irrelevant parameter in the occurrence of AOS. In fact, since we clearly observe that the composition Tb 16 Co 84 required more laser energy to switch, the presence of T M influences the switching process. Furthermore, the composition with a compensation temperature higher than room temperature (crossed by the electronic temperature under the action of the laser pulse), i.e., Tb 24 Co 76 , is the only one that undergoes switching for all laser pulse durations.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, while we have demonstrated that T M is not an essential criteria for switching, the results so far do not confirm that it is an irrelevant parameter in the occurrence of AOS. In fact, since we clearly observe that the composition Tb 16 Co 84 required more laser energy to switch, the presence of T M influences the switching process. Furthermore, the composition with a compensation temperature higher than room temperature (crossed by the electronic temperature under the action of the laser pulse), i.e., Tb 24 Co 76 , is the only one that undergoes switching for all laser pulse durations.…”
Section: Resultsmentioning
confidence: 97%
“…[18]. The choice of compositions corresponds to Tb 16 Co 84 ( ) with T M <T room ,Tb 24 Co 76 with T M >T room ( ), and Tb 32 Co 68 ( ) without a compensation point. The pump fluence in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a number of recent experiments [1][2][3][4][5][6][7][8] , it has been shown that femtosecond laser pulses can control magnetization on picosecond timescales, which is at least an order of magnitude faster compared to conventional magnetization dynamics. Among these demonstrations, the material system, GdFeCo ferrimagnetic films, is particularly interesting because deterministic toggleswitching of the magnetic order is possible without any external magnetic field.…”
Section: Main Textmentioning
confidence: 99%